Achievement Unlocked: Effective Curriculum Interventions With Low-Income Students. (January 2018) - VanTassel-Baska, Joyce
This article explores the world of curriculum intervention for gifted students from low-income and culturally diverse backgrounds. It delineates both general and specific approaches to practices that can be used in classrooms and beyond. Affective and conative concerns are addressed as they have an impact on motivation and learning. Efforts toward more positive intervention at these levels are both necessary and important to future student success and satisfaction. Breaking the cycle of poverty in respect to educational disadvantages can and should be consistently addressed and overcome.